Relationship Between Gender and the Effectiveness of Montelukast: An Italian/Danish Register-Based Retrospective Cohort Study - Sessa, Maurizio; Mascolo, Annamaria; D'Agostino, Bruno; Casciotta, Antonio; D'Agostino, Vincenzo; Michele, Fausto De; Polverino, Mario; Spaziano, Giuseppe; Andersen, Mikkel Porsborg; Kragholm, Kristian; Rossi, Francesco; Torp-Pedersen, Christian; et al. (Frontiers in Pharmacology, 2018)
Rationale: Gender-related differences in asthma prevalence, pathophysiology and clinical features induced by sex steroids have been investigated, however, how gender influences response to asthma treatments in routine clinical practice have not yet been elucidated fully. This aspect is crucial for montelukast considering the jeopardization of asthmatic patients that benefit from this treatment and the existence of evidence of gender differences in leukotriene levels. Therefore, to fulfil this medical need, we investigated the role of gender on a set of montelukast’ effectiveness surrogates in adults and paediatric patients with asthma. Methods: The study settings were Napoli 2 Local Health Unit (southern Italy) and the entire Danish territory. The study population was composed of adult and paediatric patients with asthma. Cumulative incidence curves, unadjusted and adjusted Cox regression were used as statistical models to compare aforementioned outcomes between genders. Results: Adult Italian male users of montelukast had a statistically lower persistence in montelukast treatment compared to female users. In the adjusted analyses, they had a higher hazard of montelukast’ withdrawal (Hazard Ratio [HR] 1.07; 95% Confidence Interval [CI] 1.01-1.14), add-on/switch to a long-term treatment for asthma following montelukast withdrawal (HR 1.72; 95%CI 1.39-2.12), and rescue therapy with short-acting β2 agonist (HR 1.24; 95%CI 1.04-1.47). In the adult Danish cohort, we also found that male users had higher a hazard of rescue therapy with oral corticosteroids (HR 1.10; 95%CI 1.04-1.16). In the paediatric cohorts, no statistically significant differences were observed between genders for aforementioned outcomes. Conclusions: In adults, male gender was associated with increased hazards of montelukast discontinuation, add-on/switch to a long-term treatment for asthma following montelukast withdrawal, and rescue therapy with oral corticosteroids or short-acting β2 agonist when compared to the female gender. As expected, these associations were reversed or absent in paediatric patients.